2016
DOI: 10.14740/jocmr2433w
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Body Mass Index and Dental Caries: Cross-Sectional study

Abstract: BackgroundObesity is a growing health-related problem worldwide. Both obesity and dental caries are important health issues with multifactorial aspects. Some studies have shown an association between body mass index (BMI) and caries in childhood/adolescence but limited data about such an association are available in adults. The primary goal of this study was to assess the prevalence of dental caries and its relationship to BMI.MethodsWe conducted a cross-sectional study at Taif University Outpatient Clinic, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 19 publications
4
66
2
9
Order By: Relevance
“…Another study that examined the relationship between BMI and dental caries also found no association between these variables [29], although its sample included both genders and different age group (10-12 years). However, a study conducted in Saudi Arabia [35] found partial positive correlation between BMI and DMFT analyzing men and women aged 18 years or older. Analyzing women aged 13-32 in Spain [10], the results regarding dental caries were inconclusive, since the etiology of dental caries is multifactorial and influenced by diet, oral hygiene and saliva.…”
Section: Discussionmentioning
confidence: 93%
“…Another study that examined the relationship between BMI and dental caries also found no association between these variables [29], although its sample included both genders and different age group (10-12 years). However, a study conducted in Saudi Arabia [35] found partial positive correlation between BMI and DMFT analyzing men and women aged 18 years or older. Analyzing women aged 13-32 in Spain [10], the results regarding dental caries were inconclusive, since the etiology of dental caries is multifactorial and influenced by diet, oral hygiene and saliva.…”
Section: Discussionmentioning
confidence: 93%
“…Results of poison regression model showed that primary dmft gives negative association with body mass index and positive association with permanent and overall DMFT, another study [7] also reported significant positive association between permanent DMFT and body mass index.…”
Section: Discussionmentioning
confidence: 87%
“…Studies showed that Body Mass Index (BMI) which derives from the values of mass and weight of an individual gives the association with many diseases including dental caries. A study conducted in Taif University of outpatient clinic showed that 42.2% of subjects with high prevalence of dental caries were either overweight or obese [7]. A study of Thessaloniki, Greece showed that overweight children with 1.36 times and obese children with 1.99 times were more likely to have higher dmft than normal weight children [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with previous studies (5,7). Although there are a few studies that have found an association between the two criteria (8,9). The results of the study can be justified by the fact that frequent consumption of cariogenic food is the only link between the two multifactorial entities.…”
Section: Correlations Bmi Dmft Indexmentioning
confidence: 87%